The quality and safety of washed-rind cheeses with a focus on antilisterial protection. (April 2016) - Boldyreva, Elena M.; Hill, Arthur; Griffiths, Mansel; Marcone, Massimo
Abstract: The surface microbiota of washed-rind cheeses is variable and complex. The processes involved in the production of these cheeses are not fully understood and pathogenic bacteria have been occasionally reported in the smear on the surface of the cheeses. This review describes the prevalent factors that determine development of the complex consortia of microorganisms in the smear of washed-rind cheeses, with a focus on factors that encourage or suppress growth of Listeria monocytogenes . The natural microflora in smears have been shown to exert antilisterial activities (e.g., bacteriocins), which can be utilized to develop commercial starter and smear cultures. The potential of bacteriophage to control pathogens is also being researched. A more detailed knowledge of the microbial ecology of washed-rind cheeses will reveal opportunities to maintain and improve cheese safety and quality.